Educational needs of people with type 1 diabetes mellitus and their parents: A cross‐sectional study - Mi‐Kyoung Cho; Mi Young Kim (Wiley, 2023)
Abstract Aims To investigate the educational needs of type 1 diabetes patients and their parents. Design A cross‐sectional design was employed. Methods Data were collected via an online survey and analysed by descriptive statistics and an independent t‐test. Statistical analyses were performed using IBM SPSS version 25.0. Participants comprised type 1 diabetes patients (100) and their parents (93). Results Complications management, disease characteristics and exercise were found to be the highest educational needs of type 1 diabetes patients and their parents. The following educational needs differed between patients and parents: complication management, exercise, continuous management, psychosocial needs and risk factors. Regarding psychosocial needs, social life was the most needed in terms of disease management and how to have a social life with the disease.